The microbiome-mind connection: exploring gut health’s impact on depression (Journal of Medical Science, 2025)
Introduction. The gut-brain axis is considered to be a crucial component of mental health, significantly influenced by the gut microbiota. This axis operates through neural (vagal nerve), hormonal (Hypothalamic-Pituitary-Adrenal axis), and immune pathways. Key mechanisms include microbial production of neurotransmitters like serotonin and gamma-aminobutyric acid, modulation of inflammatory responses and metabolic pathways involving short-chain fatty acids. Dysbiosis - a microbial imbalance - is associated with increased inflammation and neurotransmitter disruptions, both contributing to depressive symptoms. Material and methods. The search strategy was centered on gathering high-quality articles focusing on the gut-brain axis and its implications for mental health, particularly depression. Databases including PubMed, Scopus, and Google Scholar were searched using keywords such as "gut-brain axis," "microbiota and mental health," "depression and gut microbiome," "gut neurotransmitters," "probiotics," and "inflammation and mood disorders." Studies were selected with a focus on research published mainly within the last two years. Results. Potential interventions, such as administration of probiotics, prebiotics, dietary modifications, and innovative therapies like fecal microbiota transplantation and vagus nerve stimulation intend to restore the gut microbiota equilibrium. Conclusions. Despite the limitations of current research, such as reliance on animal models, small human sample sizes, and methodological inconsistencies, expanding these studies remains highly valuable. Conducting large-scale human trials with standardized protocols and deeper exploring the interactions of specific microbial species could create a foundation for new approaches to supporting the treatment of depression effectively.